1999
DOI: 10.1212/wnl.53.2.278
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of preferences and actual treatment choices in ALS

Abstract: Patients with ALS were able to express their preferences for life-extending or ameliorative technologies and made choices consistent with these preferences. However, patient preferences may change over time, and clinical education efforts are required throughout the course of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 9 publications
2
49
0
4
Order By: Relevance
“…Rather, a combination of optimism (7) and support (8) may determine the decisions they make about care. Preferences for care may also change over time (9) in order to accommodate to support systems and evolving perspectives on living with ALS (10).…”
Section: Dear Sirmentioning
confidence: 99%
“…Rather, a combination of optimism (7) and support (8) may determine the decisions they make about care. Preferences for care may also change over time (9) in order to accommodate to support systems and evolving perspectives on living with ALS (10).…”
Section: Dear Sirmentioning
confidence: 99%
“…70 After tracheostomy, 50% identified circumstances in which they would wish to discontinue treatment, such as having to go to a nursing home, being locked in, or becoming demented. In a prospective study, Albert et al 79 found that patients with ALS had clear preferences for or against tracheostomy and LTMV well in advance of the point of crisis and that these preferences were related to actual outcomes.…”
Section: 69mentioning
confidence: 99%
“…In quantitative studies, factors found to affect decisionmaking by pwALS in terms of NIV (and ventilation more generally) and gastrostomy include disease characteristics such as severity of symptoms [17]; demographic factors such as gender, age, educational level and IQ; and various psychological characteristics such as health beliefs, understanding of the illness, attachment to life, religiosity and mood (see [17][18][19][20][21][22][23]) as well as carer-rated everyday behavioural change indicative of executive dysfunction [17]. It has also been found that pwALS who indicate possible acceptance of NIV and gastrostomy early on in the disease trajectory are more likely to abide by their initial decision [24][25]. In addition, acceptance of gastrostomy is related to a lack of pleasure obtained from oral intake and the inability to eat independently [26].…”
Section: Introductionmentioning
confidence: 99%